Increased seizure sensitivity in pregnant mice with genetic knockdown of acid sensing ion channel 2a is associated with impaired hippocampal inflammatory response - Jones-Muhammad, Maria; Shao, Qingmei; Warrington, Junie P. (Frontiers in Physiology, 2022)
Acid sensing ion channels (ASICs) are mechano- and chemo-receptor channels that are activated by drops in extracellular pH as occurs after neurotransmission. In our previous study, we demonstrated that mice subjected to reduced utero-placental perfusion pressure during pregnancy, to mimic the pregnancy complication of preeclampsia, have reduced hippocampal expression of ASIC2a protein. We also showed that pregnant mice with heterozygous expression of ASIC2a (+/-) had increased sensitivity and severity to pentylenetetrazol-induced seizures; however, the mechanisms by which this occurs remain unclear. The purpose of this study was to investigate key molecular targets involving neurotransmission and inflammation that are differentially changed following seizure exposure in pregnant ASIC2a +/- mice. On gestational day 18.5, ASIC2a wild-type (+/+, n=7) and +/- (n=14) mice were injected with 40mg/kg pentylenetetrazol and monitored for 30 minutes. Western blot and ELISA analysis revealed no difference in hippocampal synaptosome glutamate-related proteins but an increase in GABA concentration in pregnant +/- mice. Using ELISA and multiplex assays, we found a significant decrease in serum TNFα, and a decreased concentration of pro-inflammatory cytokines and chemokines in hippocampal cytosolic fraction. Significant reductions in IL-1β, IL-3, IL-12(p70), eotaxin, interferon gamma, and macrophage inflammatory protein (MIP-1β), in the hippocampal cytosolic fractions of +/- mice were observed compared to +/+ mice. Additionally, there was no difference in hippocampal microglia density or activation in pregnant ASIC2a+/+ vs. +/- mice. These results support the hypothesis that pregnant mice with reduced ASIC2a may not be able to mount an inflammatory response following acute seizure exposure.